The Effect of Acupressure and Foot Hydrotherapy Using Red Ginger (Zingiber officinale var rubrum) on the Blood Pressure of Pregnant Women with Preeclampsia at Kembaran I Health Center - Sulistyana, Ratna (JURNAL KEBIDANAN, 2024)
Hypertension in pregnancy, particularly preeclampsia, remains a significant health issue due to its potential risks to maternal and fetal health. Despite advances in medical management, there is a need for complementary interventions to address this condition effectively. This study investigates the impact of Acupressure and Foot Hydrotherapy interventions utilizing red ginger (Zingiber officinale var. rubrum) on reducing blood pressure in pregnant women with preeclampsia at the Kembaran I Health Center. The study employs a quantitative experimental design involving 15 pregnant women diagnosed with preeclampsia. Participants were selected through non-probability sampling based on inclusion criteria: gestational age of â‰¥20 weeks and Mean Arterial Pressure (MAP) Ëƒ90 mmHg. Blood pressure was measured using a digital sphygmomanometer before and after the intervention, while an observation sheet recorded the systolic, diastolic, and MAP values. Data analysis was conducted using Paired Samples Correlations and paired sample t-tests to assess the intervention's effectiveness.Results reveal that Acupressure combined with Foot Hydrotherapy using red ginger significantly reduces blood pressure in preeclamptic women. This is evidenced by the t-test value exceeding the critical t-table value at a 5% significance level and degrees of freedom ( ), specifically 2.145. Additionally, the analysis demonstrates a high correlation between pre- and post-intervention blood pressure parameters, indicating consistent effectiveness of the therapy. This research underscores the potential of integrating complementary interventions, such as Acupressure and Foot Hydrotherapy with red ginger, into maternal healthcare protocols to manage preeclampsia and improve maternal outcomes. Further studies with larger samples are recommended to validate these findings and explore broader applications.